The challenges of male nurses in the care of female patients in Iran. (20th April 2020) - Vatandost, S.; Oshvandi, K.; Ahmadi, F.; Cheraghi, F.
Abstract : Background: Nurses professional duty mean that nurses must care for patients without gender discrimination. Meanwhile, the intrinsic differences between men and women and the need for personal contact with the patients during care procedures can create challenges for male nurses in the process of caring for a female patient. Aims: The present study aims to understand the challenges of male nurses in the care of female patients in Iran. Methods: A descriptive qualitative study was conducted with 20 male nurses selected by purposive sampling. Data were collected through unstructured and semi‐structured interviews as well as observations and were analysed using conventional content analysis,  based on the Graneheim and Lundman model. Findings: The findings revealed two main themes, including 'religious‐cultural restrictions' and 'inappropriate organizational context'. Discussion/Conclusion: Male nurses are faced with a combination of religious‐cultural and organizational challenges in providing patient care without discrimination in clinical settings. In addition to negatively affecting the quality of nursing care and satisfaction for female patients, these problems also create a stressful work environment for male nurses. Implications for health practice and policy: These problems can be alleviated in clinical settings by trying to ensure same‐gender nurses and patients, especially when performing personal care. In addition to the efforts made by nurses to present a positive and real image of themselves in caring for female patients, health policy‐makers should also attempt to improve society's attitude towards male nurses caring for female patients through the media.